Quality management for high-contact professional service firms: a multiple-case evidence from Indian law firms. Issue 2 (15th May 2020) - Prashar, Anupama
Abstract : Purpose: This paper presents an exploratory study to understand the distinctive quality dimensions of high-contact Professional Service Firms (PSFs) and develop a conceptual model for Quality Management (QM). The paper is based on empirical evidences from multiple cases in leading Indian law firms. Design/methodology/approach: The paper adopted an exploratory, multiple, embedded and comparative case study design. The empirical evidence from multiple case studies in 10 law firms (data includes 42 individual interviews, archival records, field notes) was used to explore the QM dimensions for PSFs. Findings: The results showed that QM in PSFs is a multifaceted and continuous process rather than a straightforward and episodic one. The findings reveal three distinctive dimensions of QM for PSFs: managing the firm's image; managing the client-firm interaction and support processes and; managing the perceived value of service outcome. Further, the results showed a significant variation in the design of QM practices in a relatively homogenous group of PSFs (law firms). This reflected the influence of personnel and organizational characteristics on the QM. Research limitations/implications: The research is based on evidences collected from 10 Indian law firms and the research design is exploratory in nature. The future research is suggested in terms of extending the scope and research design. Practical implications: The insights obtained from the paper have implications for managers working on the design of service operations and particularly service quality in high-contact PSFs similar to law firms. While the study does not prescribe a standard design of QM systems for PSFs, it seeks to foster the thinking of managers by helping them conceptualize the broad quality-control checkpoints and quality attributes specific to PSF settings Originality/value: The academic research in the management of professional service quality is dominated by conceptual/theoretical models for customer evaluation of service provider's performance and the issue of operationalization of QM in PSFs is still needs further investigation. This paper contributes to the theory of service operations management (SOM) by focusing on the structure of QM systems in PSFs.